2019
DOI: 10.1002/slct.201901412
|View full text |Cite
|
Sign up to set email alerts
|

Fe‐doped CoNi0.5P Hierarchical Arrays as Efficient Bifunctional Electrocatalysts for Overall Water Splitting: Evolution of Morphology and Coordination of Catalytic Performance

Abstract: Design and synthesis of bifunctional electrocatalysts with high efficient and durability for electrolytic water splitting still remain an important matter for the research of renewable energy systems. Herein, a series of CoNi 0.5 Fe x P/CC (x = 0, 0.08, 0.125, 0.25, 0.5) catalysts have been successfully prepared by a simple hydrothermal and phosphorization process, and directly used as bifunctional electrocatalysts for OER and HER. Benefiting from the suitable Fe element doping content and novel nanowire-nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…[4][5][6] The negatively charged P atoms in TMPs can not only capture protons as Lewis bases, but also effectively promote the desorption of H 2 from the active sites. Particularly, recent studies have shown that cobalt phosphides could act as bifunctional catalysts toward HER and OER, [7,8] through heteroatoms doping, [9,10] MOF coupling, [11,12] anodic electrochemical treating, [13] and hetero-structure engineering. [14] Preparation of cobalt phosphides generally involves two key procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The negatively charged P atoms in TMPs can not only capture protons as Lewis bases, but also effectively promote the desorption of H 2 from the active sites. Particularly, recent studies have shown that cobalt phosphides could act as bifunctional catalysts toward HER and OER, [7,8] through heteroatoms doping, [9,10] MOF coupling, [11,12] anodic electrochemical treating, [13] and hetero-structure engineering. [14] Preparation of cobalt phosphides generally involves two key procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing LSV curves in Figure 6a, two major conclusions could be reached: (i) the phosphide electrocatalysts apparently reveal superior OER performance to their corresponding S6 in the Supporting Information) and outperforms most of the previously reported OER electrocatalysts, including some phosphides and their composites regarding η 100 , such as NiCoP@NiMn LDH, 7 Mo-doped CoP, 33 Fe-doped CoNi 0.5 P hierarchical arrays, 34 N-doped Ni-Co phosphide, 35 Ni-Co/Ni-Fe phosphides, 36 Mo-doped NiCoP nanosheet arrays, 37 Fe-doped Ni-Co phosphide nanoplates, 38 and hollow Fe-Co-P alloy nanostructures. 39 More detailed comparisons are summarized in Table S3 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 73%
“…The FeNi-Co 2 P electrocatalyst reveals a current density of 96.2 mA/cm 2 , 137 times higher than that of Ni-Co 3 O 4 (0.7 mA/cm 2 ) and 8.9 times and 15.3 times higher than those of FeNi-Co 3 O 4 (10.8 mA/cm 2 ) and Ni-Co 2 P (6.3 mA/cm 2 ), respectively. It is noteworthy that the FeNi-Co 2 P electrocatalyst surpasses the benchmark OER catalyst RuO 2 (η 10 = 275 mV, see Figure S6 in the Supporting Information) and outperforms most of the previously reported OER electrocatalysts, including some phosphides and their composites regarding η 100 , such as NiCoP@NiMn LDH, Mo-doped CoP, Fe-doped CoNi 0.5 P hierarchical arrays, N-doped Ni-Co phosphide, Ni-Co/Ni-Fe phosphides, Mo-doped NiCoP nanosheet arrays, Fe-doped Ni-Co phosphide nanoplates, and hollow Fe-Co-P alloy nanostructures . More detailed comparisons are summarized in Table S3 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar kind of study by Wenzhuo et al . with the increased activity trend was observed in the Fe doping CoNi 0.5 Fe 0.125 P/CC as an electrocatalyst alkaline water electrolysis [132] . Here, the same kind of synthesis was followed such as hydrothermal followed by phosphorization which results sheet like morphology.…”
Section: Importance Of Fe Introduction With Metal Phosphides In the Twsmentioning
confidence: 99%